2017
DOI: 10.3389/feduc.2017.00037
|View full text |Cite
|
Sign up to set email alerts
|

50 Differences That Make a Difference: A Compendium of Frequently Confused Term Pairs in Psychology

Abstract: An adequate understanding of specialized terminology is a prerequisite for the mastery of core concepts across all scientific disciplines, including psychological science. In a previous article (Lilienfeld et al., 2015), we presented an annotated list of 50 widely used psychological terms that should generally be avoided, or at best used judiciously and with qualifications in select cases. Herein, we offer a "sequel" by presenting a list of 50 term pairs in psychology and allied fields (e.g., psychiatry, cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 116 publications
0
7
0
1
Order By: Relevance
“…While studies consistently demonstrated high inter-rater reliability of ToT measures, their discriminant validity is rarely reported. 51 The method appears to originate from a study that assessed academic performance in children with special educational needs, 52 questioning its relevance to modern classrooms. Prior to future use, ToT assessments require confirmation of construct and discriminant validity.…”
Section: Discussionmentioning
confidence: 99%
“…While studies consistently demonstrated high inter-rater reliability of ToT measures, their discriminant validity is rarely reported. 51 The method appears to originate from a study that assessed academic performance in children with special educational needs, 52 questioning its relevance to modern classrooms. Prior to future use, ToT assessments require confirmation of construct and discriminant validity.…”
Section: Discussionmentioning
confidence: 99%
“…Third, this study utilized a sample of college students to assess psychopathy. Though traits associated with psychopathy are relatively normally disbursed across the population (Lilienfeld et al 2017; Pemment, 2013), the current sample is nonclinical and may not adequately capture all aspects of psychopathy. Finally, findings from this study must be framed within the context and consideration of diversity.…”
Section: Discussionmentioning
confidence: 99%
“…1The rational for examining psychopathy, as opposed to other dimensionally constructed latent traits, like sociopathy, had to do with the use of a validated non-clinical measure of psychopathy (i.e., Levenson Self-Report Psychopathy; LSRP; Levenson et al, 1995) scale. Although many of the measured dimensions of the LSRP overlap with conceptually relevant aspects of other collective personality constructs, like sociopathy (Lillienfeld et al 2017; Pemment, 2013; Walsh & Wu, 2008), the LSRP is a well validated measure of psychopathy in nonclinical samples that can be administered by nonclinicians (Levenson et al, 1995; Sellbom, 2011). …”
mentioning
confidence: 99%
“…Ordinary least square regression models will be formulated with regard to the prediction of child and adolescent outcomes (outcomes regressed on SDQ subscales). The term "prediction" and cognate terms are used here in a statistical sense and shall not be confused with the concept of predictive validity, which describes the ability of a measure to forecast outcomes in the future [54]. To judge the statistical predictive performance of the different subscales of the SDQ (broadband vs. narrowband), the regression model with the broadband subscale (model 1: outcome regressed on broadband subscale, e.g., internalizing behavior) will be compared to the regression model with both underlying narrowband subscales jointly as predictors in one regression model (e.g., model 2: outcome regressed on emotional symptoms and peer problems).…”
Section: Statistical Analysis Strategymentioning
confidence: 99%